IMPAIRED RENAL FUNCTION AND ANEMIA IN PATIENTS WITH CHRONIC HEART FAILURE - Khusainova Munira Alisherovna (Ta’lim innovatsiyasi va integratsiyasi, 2025)
Chronic heart failure (CHF) accompanies most cardiovascular diseases and is their outcome, remaining unchanged One of the main reasons for the high level of disability and mortality of patients. Increasing heart failure over time exceeds the danger to the patient’s life of the disease that caused heart failure. Renal function has a great influence on the prognosis and outcome of CHF. Kidney failure is considered as a factor, determining the survival rate of patients with left ventricular dysfunction. Currently, the diagnosis of renal dysfunction in patients with CHF is based on the determination of concentration Serum creatinine levels, glomerular filtration rate (GFR) and/or the presence of microalbuminuria (MAU) or macroalbuminuria. At the same time, the issue of tubule function and the daily profile of renal function (daily filtration rate) in patients with CHF remains insufficiently studied. Anemia associated with CHF continues to attract the attention of researchers. This is the purpose of this work.